Unexpected arterial thrombosis and acute limb ischemia in a young male patient with COVID-19: A case report - Aljabri, Badr; Aldossary, Mohammed Yousef (Frontiers in Surgery, 2023)
Introduction The spread of severe acute respiratory syndrome coronavirus 2 has resulted in coronavirus disease 2019 (COVID-19) pandemic, raising significant concerns. COVID-19 can lead to thrombotic complications such as acute limb ischemia (ALI). In patients with COVID-19, thrombotic complications may increase the risk of morbidity and mortality. Presentation of case We report the case of a 37-year-old man who presented with a 2 weeks history of right foot pain, toes blackish discoloration, and numbness. He tested positive for COVID-19 10 days prior to his presentation. Computed tomography angiography (CTA) of the lower limbs revealed near-complete occlusion of the right popliteal artery with single-vessel posterior tibial artery runoff. The patient was brought to a hybrid operating room, and diagnostic angiography confirmed the diagnosis. He underwent popliteal artery thromboembolectomy and intraoperative thrombolysis through a posterior approach. A completion angiography demonstrated a patent popliteal artery with a 2-vessels patency to the foot. His postoperative recovery was uneventful. After surgery, the popliteal, anterior tibial, and posterior tibial arteries were all palpable. The patient was discharged home on antiplatelet therapy with frequent postoperative follow-ups during the last 1 year in our outpatient clinic. Discussion The frequency of ALI has reduced worldwide, and the hypercoagulable condition remains an infrequent cause of limb ischemia. Patients with COVID-19 have a 35%–45% thromboembolic complication rate. In many studies, the virus launches a second attack between 7 and 14 days after symptom onset, possibly causing hypercoagulability. If conservative treatment fails, various surgical methods, including thromboembolectomy, thrombolysis, and thrombosuction, can be performed to treat ALI. Conclusion In mild ALI symptoms, unfractionated heparin can be used with vigilant follow-up. Open and endovascular procedures are currently used to treat patients with acute limb ischemia, and technological advancements continue to make interventions easier and safer.